2011
DOI: 10.1007/s00264-011-1299-2
|View full text |Cite
|
Sign up to set email alerts
|

Revision hip arthroplasty using a cementless modular tapered stem

Abstract: Purpose Here we report the short-term clinical and radiological results of the Profemur®-R cementless modular revision stem. Methods Between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…By comparing all the post-operative radiographs, the extent of subsidence of the stem was evaluated using the technique of Callaghan et al 42 Significant subsidence was defined as being > 5 mm. 16,27 The femoral score of Barnett and Nordin 43 was calculated immediately post-operatively and at the five-year follow-up examination in order to analyse the formation of bone in the 14 The sum of the thicknesses of the medial and lateral cortices of the shaft at the level below the lesser trochanter, where the inner and outer rims of the cortex are parallel, was divided by the total diameter of the shaft at that level and the result multiplied by 100. 43 The difference between the Barnett and Nordin-Score five years after the operation and the immediate post-operative score was used to calculate the amount of proximal bone formation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing all the post-operative radiographs, the extent of subsidence of the stem was evaluated using the technique of Callaghan et al 42 Significant subsidence was defined as being > 5 mm. 16,27 The femoral score of Barnett and Nordin 43 was calculated immediately post-operatively and at the five-year follow-up examination in order to analyse the formation of bone in the 14 The sum of the thicknesses of the medial and lateral cortices of the shaft at the level below the lesser trochanter, where the inner and outer rims of the cortex are parallel, was divided by the total diameter of the shaft at that level and the result multiplied by 100. 43 The difference between the Barnett and Nordin-Score five years after the operation and the immediate post-operative score was used to calculate the amount of proximal bone formation.…”
Section: Methodsmentioning
confidence: 99%
“…[19][20][21][22][23][24] The incidence of subsidence and peri-prosthetic fracture of modular curved stems (MRP-Schaft, Peter Brehm, Weisendorf, Germany; Profemur-RSchaft, Wright Medical, Arington, Tennessee; Revitan Curved, Zimmer GmbH) has been reported to be between 0.8% and 17.1%, and 0% and 11.7% respectively. 3,4,7,8,[25][26][27][28][29] Two surgical techniques have been described for the introduction of modular curved, distally fixed stems. Either the fixation bed for the prosthesis is prepared with a cylindrical reamer alone (Brehm-MRP-Schaft, Profemur-R-Schaft) and results in cone-in-cylinder fixation; or the medullary cavity is first reamed with a cylindrical tool and then cone-in-cone fixation is obtained with a conical rasp (Revitan Curved).…”
mentioning
confidence: 99%
“…The high failure rate of cemented acetabular components in revision THA due to failure of interdigitation of cement into the sclerotic host bone has led to the increased use of cementless fixation [1][2][3][4][5]. Small contained defects can usually be treated with porous hemispherical cups with supplemental bone grafting [6].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Traina et al reported no modular neck fractures in 88 THRs with a mean follow-up of nine years [21]. Pattyn et al also reported no modular neck fractures for 68 revision THRs performed using a revision femoral stem from the same manufacturer with identical modular necks [22]. These results suggest that modular neck fracture is not a prominent failure mode for the subject femoral stem or modular neck design.…”
Section: Modular Neck Fracturesmentioning
confidence: 54%